Education Studies in South Africa The Quest for Relevance, Rigour and Restructuring - Wolhuter, Charl C. (AOSIS, 2020)
The thesis of this volume is that the fields of scholarly enquiry of Education - internationally as well as in South Africa in particular - despite being fields of virile scholarly activity and output, are in need of a major overhaul. In this collected work this want in research is encapsulated in three words: relevance, rigour and restructuring. Research in the scholarly field(s) of Education is predominantly of small scale, non-accumulative, widely condemned as not of a comparable standard to research done in other social sciences, much less upon a par with research in the natural sciences, and lacking structure in the sense of being anchored in a firm theory. To make matters worse, scholars in Education internationally and in South Africa have till very recently eschewed discussion as to the packaging or structuring of knowledge produced by Education research. The book consists of chapters containing original research unpacking these desiderata from a variety of angles. The authors had them served by a variety of methods, from deductively argued position papers, to empirical research, the latter both quantitative (survey research) and qualitative.